Titration Calorimetry From Concept to Application - Hansen, Lee D. (SpringerBriefs in Molecular Science,, 2018)
This Brief describes the calibration of titration calorimeters (ITCs) and calculation of stoichiometry, equilibrium constants, enthalpy changes, and rate constants for reactions in solution. A framework/methodology for model development for analysis of ITC data is presented together with methods for assessing the uncertainties in determined parameters and test data sets. This book appeals to beginners, as well as to researchers and professionals in the field.